2011
DOI: 10.1088/0004-637x/737/2/61
|View full text |Cite
|
Sign up to set email alerts
|

THE ATACAMA COSMOLOGY TELESCOPE: SUNYAEV-ZEL'DOVICH-SELECTED GALAXY CLUSTERS AT 148 GHz IN THE 2008 SURVEY

Abstract: We report on 23 clusters detected blindly as Sunyaev-Zel'dovich (SZ) decrements in a 148 GHz, 455 deg 2 map of the southern sky made with data from the Atacama Cosmology Telescope 2008 observing season. All SZ detections announced in this work have confirmed optical counterparts. Ten of the clusters are new discoveries. One newly discovered cluster, ACT-CL J0102−4915, with a redshift of 0.75 (photometric), has an SZ decrement comparable to the most massive systems at lower redshifts. Simulations of the cluster… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
227
1
1

Year Published

2013
2013
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(238 citation statements)
references
References 65 publications
(115 reference statements)
7
227
1
1
Order By: Relevance
“…Similar results drawn from smaller samples of clusters spreading over a wider range of redshifts derived by SPT (Andersson et al 2011) and ACT (Marriage et al 2011) also agree with the Planck findings. It is, however, important to test the effects of clumping or assumptions of hydrostatic equilibrium by comparing to observations that are not related to the ICM.…”
Section: The Intrinsic Scatter In the Dsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar results drawn from smaller samples of clusters spreading over a wider range of redshifts derived by SPT (Andersson et al 2011) and ACT (Marriage et al 2011) also agree with the Planck findings. It is, however, important to test the effects of clumping or assumptions of hydrostatic equilibrium by comparing to observations that are not related to the ICM.…”
Section: The Intrinsic Scatter In the Dsupporting
confidence: 84%
“…Hincks et al (2010), Vanderlinde et al (2010) and Marriage et al (2011) reported more blind cluster detections (each ∼20 candidates), setting the stage for SZ selected cluster catalogs.…”
Section: Sz Scaling Relations: First Results From Large Dedicated Sz mentioning
confidence: 99%
“…Unfortunately, achieving sufficient sensitivity to detect low mass clusters in SZ is technologically very challenging. For instance, the current SPT, ACT, and Planck surveys are expected to be complete at all redshifts above mass thresholds of 7 × 10 14 M ⊙ , 10 15 M ⊙ , and 2 × 10 15 M ⊙ respectively (Vanderlinde et al, 2010;Marriage et al, 2011;Planck Collaboration et al, 2011a); while these limits will go down, they will not reach thresholds comparable to those of X-ray or optical cluster selection. Consequently, while these experiments are currently the best avenue to probe the z ≈ 1 massive cluster population, on a 3 − 5 year time scale the focus of cluster detection is likely to shift towards optical and X-ray.…”
Section: Cluster Findingmentioning
confidence: 99%
“…The first three successful cluster SZ surveys -using the South Pole Telescope (SPT), the Atacama Cosmology Telescope (ACT), and the Planck satellite -are all currently ongoing. All three projects have released SZ-selected cluster samples (Vanderlinde et al, 2010;Marriage et al, 2011;Planck Collaboration et al, 2011a;Williamson et al, 2011;Reichardt et al, 2013). These samples tend to be of very massive clusters (see Figure 27) and, in the case of ACT and SPT, extend to z ≈ 2, with the upper limit set by the lack of massive galaxy clusters above this redshift.…”
Section: The Current State Of Playmentioning
confidence: 99%
“…For this, data from optical and X-ray cluster surveys are currently used to constrain cosmological parameters. Recently, however, a new window of information regarding galaxy cluster physics has opened with the release of cluster surveys (e.g., Staniszewski et al 2009;Marriage et al 2011;Williamson et al 2011;Planck Collaboration VIII 2011;Reichardt et al 2013) that make use of the SZ effect, which is a signature that does not diminish with luminosity distance because it is nearly independent of redshift. In fact, thermal SZ signal is a tracer of the total thermal energy of the hot (∼10 7 K) intracluster gas, therefore it is correlated to the mass of the cluster.…”
Section: F Gasmentioning
confidence: 99%